Behavioral Finance in Sharia Investment: An Empirical Study on Indonesian Millennials - Abdul Rozak; Abdul Rozak; Nugraha; Maya Sari; Imas Purnamasari; Fakhrul Anwar Zainol (Journal of Islamic Economics and Business, 2024)
The increasing participation of millennials in Indonesia’s Islamic financial markets underscores the importance of understanding the behavioral factors that influence their investment decisions. This study aims to analyze the impact of behavioral biases specifically representativeness, overconfidence, and herding on Sharia-compliant investment behavior among millennial investors. Despite the growing relevance of behavioral finance, empirical research on cognitive biases in Islamic investments remains limited, particularly in emerging economies. This study fills that gap by employing Structural Equation Modeling–Partial Least Squares (SEM-PLS) to examine data collected from 300 millennial users of the Bibit Sharia investment platform in West Java. The findings reveal that overconfidence (β = 0.235, p < 0.05) and herding (β = 0.198, p < 0.05) significantly influence investment decisions, whereas representativeness bias has no significant effect (p > 0.05). These results highlight the critical role of self-confidence and social influence in shaping millennial Sharia investment behavior. The study recommends enhancing targeted financial literacy programs that address behavioral biases and promote ethical, independent decision-making among young Muslim investors. Future research is encouraged to include broader regional samples and explore additional behavioral factors within Islamic financial contexts.